A robust active control scheme for automotive engine vibration based on disturbance observer. (May 2020) - Naseri, Rahime; Talebi, Heidar Ali; Ohadi, Abdolreza; Fakhari, Vahid
Abstract: In this paper, a combination of robust active controller and disturbance observer for active engine mounts is proposed as an effective way to improve driver comfort for automotive vehicles. First, a robust controller based on μ -synthesis is designed for the engine mounting system in the presence of parametric uncertainty. The effectiveness of the μ -controller in satisfying robust stability and performance is demonstrated. To further improve the performance of vibration control, an observer is designed where all system states and unknown disturbances are estimated. The estimated disturbance forces are used as control signals to cancel the unwanted effects of these disturbances. The results of the system behavior at different engine speeds clearly demonstrate a significant improvement of the system performance as a result of applying the system observer. Highlights: The μ -controller guarantees the robust stability in the presence of uncertainties. An observer is designed to estimate disturbances without using additional sensors. The hybrid control method is used to overcome the limitations of robust controller. A remarkable performance improvement is obtained as compared to other studies.